Effect of Drip-Applied Metam-Sodium and S-Metolachlor on Yellow Nutsedge and Common Purslane in Polyethylene-Mulched Bell Pepper and Tomato. (20th June 2017) - Dayton, Daniel M.; Chaudhari, Sushila; Jennings, Katherine M.; Monks, David W.; Hoyt, Greg W.
Abstract : Field studies were conducted to determine the effect of metam sodium and S -metolachlor applied through drip irrigation on yellow nutsedge, common purslane, bell pepper, and tomato (injury and yield) in plasticulture. Treatments consisted of weed-free, weedy, S -metolachlor alone at 0.85 kg ha -1, methyl bromide, metam sodium (43, 86, 176, and 358 kg ai ha –1 ) alone, and metam sodium (43, 86, 176, and 358 kg ai ha –1 ) followed by S -metolachlor at 0.85 kg ha –1 . Metam sodium and S -metolachlor was applied preplant 2 wk before and 2 wk after transplanting (WAT) through drip irrigation, respectively. No injury was observed to bell pepper and tomato from metam sodium alone, or metam sodium fb S -metolachlor treatments. With the exception of yellow nutsedge density 15 WAT in bell pepper, herbicide program did not influence yellow nutsedge and common purslane density at 4 and 6 WAT and bell pepper and tomato yield. At 15 WAT, yellow nutsedge density was lower in treatments that received metam sodium fb S -metolachlor compared to those treatments that only received metam sodium. Drip-applied metam sodium at 176 and 358 kg ha –1 in both bell pepper and tomato provided similar control of common purslane, and yellow nutsedge, produced comparable yields, and failed to elicit any negative crop growth responses when compared to MeBr. In conclusion, metam sodium at 176 and 358 kg ha –1 fb S -metolachlor 0.85 kg ha –1 is an effective MeBr alternative for season long weed control in plasticulture bell pepper and tomato.